The Effectiveness of Infection Prevention Control Nurse (IPCN) Supervision in Improving Safe Injection Compliance at RSUD Dr. R. Koesma Tuban (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Background: Compliance with safe injection standard operating procedures (SOP), in accordance with WHO recommendations, is an effort to prevent and control healthcare-associated infections. This is in line with the global commitment to improving the safety of patients and healthcare workers. Supervision is a reinforcing factor to improve compliance in performing safe intravenous injections. Method: The type of this research is correlational with a cross-sectional time approach. The respondents used in the study were 68 nurses and were selected using the cluster random sampling technique. The instrument used in data collection was a checklist. Result: The results of the statistical test using Chi Square with a significance level of α < 0.05 obtained a value of ρ = 0.001 < 0.05 with a correlation coefficient of r = 0.405, indicating a relationship between the two variables, categorized as moderate with a positive correlation. Conclusion: The conclusion of this study indicates a relationship between the implementation of IPCN supervision and efforts to improve safe intravenous injection practices at RSUD dr. R. Koesma Tuban.